Age Differences in Language Segmentation. Issue 1 (1st January 2016) - Stine-Morrow, Elizabeth A. L.; Payne, Brennan R.
Abstract : Reading bears the evolutionary footprint of spoken communication. Prosodic contour in speech helps listeners parse sentences and establish semantic focus. Readers' regulation of input mirrors the segmentation patterns of prosody, such that reading times are longer for words at the ends of syntactic constituents. As reflected in these "micropauses, " older readers are often found to segment text into smaller chunks. The mechanisms underlying these micropauses are unclear, with some arguing that they derive from the mental simulation of prosodic contour and others arguing they reflect higher-level language comprehension mechanisms (e.g., conceptual integration, consolidation with existing knowledge, ambiguity resolution) that are common across modality and support the consolidation of the memory representation. The authors review evidence based on reading time and comprehension performance to suggest that (a) age differences in segmentation derive both from age-related declines in working memory, as well as from crystallized ability and knowledge, which have the potential to grow in adulthood, and that (b) shifts in segmentation patterns may be a pathway through which language comprehension is preserved in late life.